Illegalisms and discipline in a Brazilian prison - Andre Ribeiro Giamberardino (Oñati Socio-Legal Series)
The article summarizes research with an empirical sample of all cases of severe disciplinary misconduct for possessing a cell phone in a prison of Curitiba in 2017. The question posed for analysis is which parameters would determine the imputation of disciplinary responsibility for cell phones seized from this or that prisoner. From the study of the processes and participant observation, it becomes evident how, in the great majority of cases, the prisoners who take responsibility for the seized items do so because they do not have family in the region, because they have a high remnant penalty or to get some form of payment, not being the real owners of the devices. The application of the disciplinary sanction, with knowledge of the falsity of the confession, indicates that prison administration operates as a manager of illegalisms and not from the legal/illegal binomial.